A methods engineering study on Tahanang Walang Hagdan (TWH) Metal Craft Department - De Jesus, Eleanor; Gamolo, Arturo; Gito, Gilmour (Diliman, Quezon City College of Engineering, 2001)
The Tahanang Walang Hagdanan (TWH) metal craft department is a manufacturing branch of the Tahanang Walang Hagdanan, which deals with the manufacturing of wheelchairs. It currently produces six types of wheelchairs, which they supply to PCSO and other hospitals in Manila. The study is centered on methods improvement and on the effectiveness and ease in production that can be attained by its manufacturing department. Methods documentation and analysis were done through actual plant visits and through the employment of various tools and techniques learned in The IE 32 course. The study addressed the following problems : no definite production flow line, machine failures, injuries and accidents, inefficient materials handling. It is the task of this study to come up with the possible solutions to the aforementioned problems. The group came up with at least three possible solutions or alternatives for each problem identified, depending on its MUST and WANT rating. For production flow line, the group conducted an SLP (Systematic Layout Planning) to provide for a clearer and better work area layout. A Maintenance Team is deemed very favorable as evaluated by the group to answer the problems involving machine failure. With regards to the frequency of injuries and accidents, the group suggested having a strict implementation of their safety guidelines so as to minimize the occurence of this problem. Finally, a low lift pallet trolley was suggested to facilitate the materials handling aspect of the company. The chosen alternatives are subjects for implementation, wherein the group suggested some means of attaining and implementing those alternatives with the least possible implementation costs. The suggested solutions to the problems are evaluated with the factors regarding low cost but high productivity or a justifiable combination of cost versus productivity. Implementation suggestions for the productions flow line, machine maintenance, and injuries and accidents would prove to be of very little cost to the company upon implementation and can promise very becoming results regarding productivity. The cost that is mainly required is of only alloting enough time for the project. Improvement on the materials handling cost can be justified through the elimination of losses in time and money due to material transportation. The implementation of these plans ranges from duration of one to three months and is attainable within the given scope of implementation stated in this study.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Metal-cutting.; Systems analysis